(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
The study was conducted to analyze body shape variations between sexes of G. giurisin different collection sites in Norzagaray River, Bulacan, Philippines using the tools of geometric morphometrics (GM), a combination of advanced different statistical tests to describe variations in shapes. The comparative study of G. giurispopulation structure using landmark-based morphometrics can be the reliable tool to describe variations in population structures of the fish from different areas of the river. The fish were collected and scanned for image capturing. After image capture, the fishes collected were preserved, dissected following the protocol of identification, authentication and gender determination by the Bureau of Fisheries and Aquatic Resources (BFAR) - Region III, Maimpis City, Pampanga, Philippines. The images of collected individuals of G. giuris were subjected to landmarking to obtain the x and y coordinates of the landmarks using the TpsRelw software. The raw coordinates were subjected to procrustes-fitting to superimpose the different orientation and position of the specimens. Relative warps Score generated by the TpsRelw were subjected to different statistical tests such as MANOVA, Discriminant Function Analysis and Canonical Variate Analysis. Results showed no differences in body shapes between sexes of G. giuris although variation within sexes were found to be the major contributor for the differences observed populations. This study has shown that GM is a useful tool to be able to quantitatively describe variations in populations.